Conservation and fishery management regulations of Jack mackerel Trachurus murphyi in Peru - Zuzunaga, Jorge (2013)
The Peruvian fisheries exploit renewable natural resources and as such are regulated by a legal framework aiming at ensuring their conservation and sustainable use. The General Fisheries Act, DL N°. 25977, points out that fisheries management systems shall be established for each type of fishery taking into account to the state of exploitation of the fishery resources, reconciling the principles of sustainability and long-term conservation with those aiming at the attainment of the maximum possible economic and social benefits. According to the provisions of the Fisheries Management Regulations approved by SD N°. 011-2007-PRODUCE, the management of the Jack mackerel Trachurus murphyifisheries includes among others, a fishing access regime that regulates the fleet size and the allocation of fishing licenses, which can only be granted to vessels fishing only for direct human consumption. The obligation to allocate the resources sardine Sardinops sagax, Jack mackerel T. murphyi, and mackerel Scomber japonicus, for direct human consumption has been in force since September 2002, following the ruling established by SD N°. 001-2002-PRODUCE. Other measures currently in force include those establish a minimum mesh size, the ban to catch or land specimens under 31 cm total length limit, the opening and closing of the fishing seasons, and catch limits or annual quotas. These provisions are supplemented by measures for monitoring, control and surveillance, and for the effective conservation and sustainable use of the fishery resources.